GADD45 proteins: central players in tumorigenesis - Tamura, Rodrigo Esaki (2012)
The Growth Arrest and DNA Damage-inducible 45 (GADD45) proteins have been implicated in regulation of many cellular functions including DNA repair, cell cycle control, senescence and genotoxic stress. However, the pro-apoptotic activities have also positioned GADD45 as an essential player in oncogenesis. Emerging functional evidence implies that GADD45 proteins serve as tumor suppressors in response to diverse stimuli, connecting multiple cell signaling modules. Defects in the GADD45 pathway can be related to the initiation and progression of malignancies. Moreover, induction of GADD45 expression is an essential step for mediating anti-cancer activity of multiple chemotherapeutic drugs and the absence of GADD45 might abrogate their effects in cancer cells. In this review, we present a comprehensive discussion of the functions of GADD45 proteins, linking their regulation to effectors of cell cycle arrest, DNA repair and apoptosis. The ramifications regarding their roles as essential and central players in tumor growth suppression are also examined. We also extensively review recent literature to clarify how different chemotherapeutic drugs induce GADD45 gene expression and how its up-regulation and interaction with different molecular partners may benefit cancer chemotherapy and facilitate novel drug discovery.